Islamic Education As The Foundation Of Character Education At Kalimanggis Public Elementary School, Kaloran Temanggung - Eny Rahmawati; Joni; Mahsun; Ahmad Aji Pangestu; Eri Cahyanti; Husna Nashihin; Rhindra Puspitasari; Siti Qomala Hayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study employs a descriptive qualitative method with an interpretative approach that focuses on understanding the meanings behind data obtained from real-life contexts. This method aims to describe phenomena in depth without manipulating variables or field conditions. Data analysis is carried out through three main stages—data reduction, data presentation, and conclusion drawing—all intended to gain a comprehensive and valid understanding. The findings indicate that Islamic education plays a crucial role as the primary foundation in shaping students’ character. Islamic teachings emphasize not only the mastery of knowledge but also the strengthening of moral and spiritual values that serve as life guidance. This form of education fosters a balance between intellectual, emotional, and spiritual intelligence, thereby shaping individuals who are faithful, noble in character, and responsible toward themselves and society. The values of exemplary conduct and religious moderation serve as essential principles in the character-building process, where teachers and the educational environment act as real-life role models for students. The implementation of Islamic education is realized through the integration of Islamic values into teaching and learning activities as well as school culture, ensuring that character values are not merely taught but also internalized in daily life. Thus, Islamic education proves to be a comprehensive educational system that is relevant to contemporary challenges and effective in shaping a generation of strong character, knowledge, and virtuous conduct.